A data-driven fault-tolerant control design of linear multivariable systems with performance optimization. (September 2017) - Li, Zhe; Yang, Guang-Hong
Abstract: In this paper, an integrated data-driven fault-tolerant control (FTC) design scheme is proposed under the configuration of the Youla parameterization for multiple-input multiple-output (MIMO) systems. With unknown system model parameters, the canonical form identification technique is first applied to design the residual observer in fault-free case. In faulty case, with online tuning of the Youla parameters based on the system data via the gradient-based algorithm, the fault influence is attenuated with system performance optimization. In addition, to improve the robustness of the residual generator to a class of system deviations, a novel adaptive scheme is proposed for the residual generator to prevent its over-activation. Simulation results of a two-tank flow system demonstrate the optimized performance and effect of the proposed FTC scheme. Highlights: The canonical form identification technique is introduced to design the data-driven residual generator. The Youla parameters are tuned iteratively based on the online system data for fault-olerant control. A novel adaptive law is developed for the proposed residual generator to avoid the over-activation of the FTC mechanism.